Role of zinc in febrile seizures - B, Sreenivasa; Kumar P, Sunil; B, Manjunatha (International Journal of Contemporary Pediatrics, 2017)
Background: Febrile convulsion is the most common type of seizures in childhood. Zinc has been studied in the context of pathophysiology of febrile seizure. The objective of the present study was to compare the serum zinc levels in children with febrile seizure, acute febrile illness without seizure and in healthy children. Methods: The present study was a cross sectional study. A total of 150 infants and children aged between 6 months to 5 years fulfilling the inclusion criteria were included. The study comprised of 3 groups - Group A: Children with febrile seizures (50 cases), Group B: Children with only fever, but no seizures (50 cases) and Group C: Healthy children (50 cases). Serum zinc was measured by colorimetric method and compared among the groups using statistical methods. Results: There was no significant difference in sex, age, weight, height and head circumference between the three groups (P >0.05). There was no statistically significant difference between the groups regarding temperature at admission. Mean serum zinc level was 50.49 ± 15.17 µgm/dl, 61.53 ± 16.87 µgm/dl and 85.70 ± 20.76 in Group A, Group B and Group C respectively. It was significantly lower in Group A compared to Group B, it was significantly lower in Group B compared to Group C. Serum zinc level was less than 65 µgm/dl in 65% children in Group A and 35% in Group B. Conclusions: Serum zinc level was lower in children with simple febrile seizures as compared to children with acute febrile illness and healthy children which were found to be statistically significant.